Skrining Fitokimia, Aktivitas Antibakteri, dan Antijamur Ekstrak Etil Asetat Biji Lamtoro (Leucaena leucocephala) - Dewa Ayu Mas Maharani; Anak Agung Gede Indraningrat; Ni Wayan Widhidewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
The entry of bacteria and fungi into the body is one of the causes of infectious diseases. However, the use of synthetic antibiotics and antifungals often causes resistance effects by pathogenic microorganisms. One effort to overcome bacterial and fungal resistance is to explore secondary metabolite compounds from herbal plants and one of them is the seeds of the lamtoro plant (Leucaena leucocephala). Previous research has reported the antibacterial potential of lamtoro seeds. However, the information reported is not comprehensive because it was only tested using ethanol solvent. Apart from that, research on the antifungal activity of lamtoro seeds has never been reported. This research design uses laboratory experimental methods. The initial stage is plant identification and continued with extraction of lamtoro seed simplicia using ethyl acetate solvent with a ratio (1:5 w/v) for 24 hours and simplicia remaceration is carried out again for 24 hours. The resulting extract will be tested for its phytochemical content. Next, the extract will be tested for antibacterial and antifungal activity using the Kirby-Bauer method. The test bacteria used were Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Streptococus mutans FNCC 0405, and Klebsiella pneumoniae ATCC 700603. The test fungi used were Candida albicans and Aspergillus flavus. The results of phytochemical screening showed that the ethyl acetate extract of lamtoro seeds contained flavonoids, saponins and tannins. Meanwhile, the antibacterial activity test of the ethyl acetate extract of lamtoro seeds showed that there was no antibacterial inhibitory effect on Gram-negative or Gram-positive bacteria. The antifungal screening showed that the extract did not display antifungal activity against tested fungal indicators.